Agama dan Perubahan Masyarakat Menurut Malik Bennabi - Syihab, Usman (Afkar: Jurnal Akidah dan Pemikiran Islam, 2009)
This article studies Malek Bennabi’s concept on social change. It analyzes Malik Bennabi’s idea of the three realms; realm of thing, realm of figure and realm of idea, and their significance as a dialectical basis of social change. The article tries to investigate the role of religion in changing societal dimension from the realm of thing to the realm of ideas. This article also reveals the importance of both negative and positive approaches for building positive social cultures according to Malik Bennabi.